2016
DOI: 10.1016/j.jfma.2016.10.011
|View full text |Cite|
|
Sign up to set email alerts
|

Morbidity and mortality of very low birth weight infants in Taiwan—Changes in 15 years: A population based study

Abstract: Although the mortality and most of the morbidity of VLBW infants improved over time, the incidence of ROP remained constant. This requires us to further evaluate our strategy for preventing ROP in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 12 publications
3
25
0
1
Order By: Relevance
“…11 The most commonly reported risk factors were BW and GA. 7,[12][13][14] Although some articles using national datasets have been reported, few studies have been conducted in Asian populations. [15][16][17] Previous ROP studies in Asian populations were also limited by small sample sizes or constrained by specific ranges of BW. [15][16][17] The National Health Insurance Research Database (NHIRD) in Taiwan contains extracted claims data from all ambulatory and in-hospital patients.…”
Section: Resultsmentioning
confidence: 99%
“…11 The most commonly reported risk factors were BW and GA. 7,[12][13][14] Although some articles using national datasets have been reported, few studies have been conducted in Asian populations. [15][16][17] Previous ROP studies in Asian populations were also limited by small sample sizes or constrained by specific ranges of BW. [15][16][17] The National Health Insurance Research Database (NHIRD) in Taiwan contains extracted claims data from all ambulatory and in-hospital patients.…”
Section: Resultsmentioning
confidence: 99%
“…The data used for Taiwan were adapted from Su et al (29), who reported on the classified comparison of the 1997–2001, 2002–2006, and 2007–2011 reports in Taiwan.…”
Section: Data Collectionmentioning
confidence: 99%
“…1 shows the summary of the data from the KNN (10) in 2015 and Taiwan in 2007–2011 (29). Taiwan's national data were added here, and the SRs of the VLBWIs were 76.4%, 81.5%, and 85.1% in divisions of 1997–2001 (4,647), 2002–2006 (4,005), and 2007–2011 (4,507), respectively (29). As shown in Fig.…”
Section: International Comparison Of Neonatal Srs Of Vlbwis and Elbwismentioning
confidence: 99%
“…91 The results of others have been contradictory in this respect. 25,83,90,98,[218][219][220] Some claim that the incidence is probably unchanged, and that variations depend on the confusion over how to define NEC, 198,203,221 which, with its multifactorial aetiology, is rather the common result of several pathophysiological pathways than one disease entity. 18 Apart from discrepancies in case definition and the inclusion or exclusion of mild cases, possible explanations for variations of NEC incidence within and between populations may be differences in the composition of populations in terms of gestational ages, distribution of risk factors, protective factors, and comorbidities, as well as clinical practices.…”
Section: Variations Over Time and Between Populationsmentioning
confidence: 99%